Experimental analysis of an attenuation method for Hydrodynamic Ram effects. (5th October 2018) - Artero-Guerrero, J.A.; Varas, D.; Pernas-Sánchez, J.; López-Puente, J.
Abstract: The Hydrodynamic Ram (HRAM) phenomenon occurs when an object with a high-kinetic energy impacts against a fluid-filled structure, which could induce important damages. An attenuation technique would be of great interest for structures which could be subjected to impact. In this work, honeycomb panels are used to fill the entire space inside the structure in such a way that they are able to alleviate the loading onto it. Experimental tests were carried out varying aluminium honeycomb cells orientation, to determine the configuration that mitigates more efficiently the effects of HRAM comparing the results with a non-protected structure. The experimental tests were analysed using a high speed video camera, strain gauges, residual displacement of the structure walls and the deformation of the honeycomb panels. It is shown that for all the configurations, the honeycomb is able to reduce the plastic deformation of the structure. The honeycomb allows to reduce the cavity expansion in the fluid, which is the most dangerous phenomenon in the studied cases. The best configuration is able to diminish up to 54% the residual expanded volume in the structure walls, and hence considerably attenuating the HRAM effect on the structure. Graphical Abstract: Highlights: HRAM damaging effects on aluminum tubes has decreased up to a 54% using aluminum honeycomb as attenuation method. The greatest attenuation is achieved using the cell orientation in which the cells wrap the cavity as it evolves. For the best configuration, in which the cells wrap the cavity, the dominant failure mechanisms cell wall buckling which lead to a higher resistance.